Impact of Corporate Name Change on Stock Prices: Evidence from BSE - Goyal, Priyanka; Goyal, Mansi (Gyan Management Journal, 2023)
The study examines the impact of the corporate name change on stock  prices. By employing the event study methodology, efforts have been  made to analyze how the market reacts to the corporate name change  of companies during the years 2019 and 2020 listed on the Bombay  Stock Exchange (BSE). The results suggested that corporate name  change hardly impacts stock prices and shareholders’ wealth. Our  findings also indicated that investors are rational in India. The t-test  has been used to test the significance of the results. The study adds to  the literature as few studies have been conducted in the Indian context  that analyzed the impact of the corporate name change on stock  market reactions and has provided inconclusive results.
Keywords: Event study methodology; Corporate name change; Shareholder’s wealth; Abnormal returns